Critical Discourse Analysis of American Ideology Towards Qatar Isolation in Selected USA Editorials - Abid, Hashim Garbet; Mohammad, Manal Jasim (Al-Adab Journal, 2022)
This study investigates the representation of Qatar isolation by Arab Quartet in selected USA editorials, i.e., it is represented positively or negatively. Those editorials involve The New York Times, The Washington Post and The Wall Street Journal. It explores the role of editorials in moulding, shaping and reshaping of ideology. It tries to find out the hidden ideologies in discourse of these editorials. The study follows a multidisciplinary approach of CDA starting with an overview of CDA shedding light on its roots, critical meaning, It focuses on the theory of ideology giving its definitions, its history, its structure and forms, as well as the mechanisms through which it works. The present study adopts an eclectic model of van Dijk (1991) and Fairclough (1989) which deploys linguistically three different tools to analyze (56) selected texts of the editorials. These tools include syntactic modality, semantic presupposition and stylistic hyperbole.The results reveal that Qatar isolation is represented negatively rather than positively, which means that editors view Qatar and the U.S as one group ideology and Arab Quartet as its opposite ideology. This indicates the U.S underlying ideology and ideological reverberations such as hegemony, dominance and superiority. It also verifies van Dijk’s (1991) and Fairclough’ (1989) model as a powerful tool within CDA to reveal hidden ideologies and ideological mechanisms.